Vitamin D supplements in pregnant Asian women: effects on calcium status and fetal growth. Issue 6216 (15th March 1980) - Brooke, O G; Brown, I R; Bone, C D; Carter, N D; Cleeve, H J; Maxwell, J D; Robinson, V P; Winder, S M
Abstract : In a double-blind trial of vitamin D supplements in pregnant Asian women calciferol (ergocalciferol, 1000 IU/day) was administered to 59 women and placebo to 67 controls during the last trimester. The two groups had similar distributions of maternal age, height, parity, number of vegetarians, countries of origin, and sex and gestation of the infants. At entry to the trial maternal serum 25-hydroxy vitamin D (25-OHD) concentrations were low in both treatment and control groups and significantly lower in vegetarians than non-vegetarians. Mothers in the treatment group gained weight faster in the last trimester than those in the control group, and at term they and their infants all had adequate plasma 25-OHD concentrations, Mothers and infants in the control group, however, had low plasma concentrations of 25-OHD and calcium and raised plasma alkaline phosphatase (bone isoenzyme) activity. Five of these infants developed symptomatic hypocalcaemia. Almost twice as many infants in the control group were small for gestational age (29% v 15%), but there were no significant differences between the two groups of infants in antropometric measurements. Infants in the control group, however, had larger fontanelles, suggesting impaired ossification of the skull. Because of the benefits to mothers and infants in the treatment group and the absence of side effects, vitamin D supplements should be given to all pregnant Asian women in the United Kingdom.